(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2025)
Central Asia is in the heart of Europe and Asia: a historical oasis of cultural ties and migration flows through the ages. Its landscapes, encompassing vast steppes to the mountain peaks and hot deserts of Kazakhstan, Kyrgyzstan, Uzbekistan, Turkmenistan and Tajikistan, represent a complex legacy of migration. Throughout history, Central Asia has been a bridge between East and West. The Silk Road era left an indelible mark on the diverse peoples of the region, including Scythians, Mongols, Turkic tribes, and mixed ethnic groups. Understanding these migration processes can provide valuable information about the region’s emerging identity and socio-economic development. Constant research is necessary for migration processes as means of survival, not as a static phenomenon. There are currently complex geopolitical processes, specifically concerning the conflict between Ukraine and Russia, the role of this region will acquire a new meaning and character, and the changes that will occur will have an impact on migration processes. The purpose of this study is to determine what changes migration processes have undergone in the Central Asian region, especially for the period from 2022 to the present day, what problems the countries of this region may face and what solutions need to be implemented in the migration policy of these countries. This study will help to understand the migration processes that have taken place over the past years both for citizens of the countries of this region and for researchers interested in migration and economies of the countries of the Central Asian region. The relevance of the study of migration trends in Central Asian states over the last decades is due to a number of factors that have a significant impact on the socio-economic and political development of the region, and global migration processes relying on geopolitical significance of the region, economic transformation, social and demographic changes, international relations and integration and security issues. Key words: migration processes, Central Asian region, social transformation, remittances, displaced people